Intellectual journeys - Andries, L (Voltaire Foundation, 2017)
The exchange of ideas between nations during the Enlightenment was greatly facilitated by cultural ventures, commercial enterprise and scientific collaboration. But how were they exchanged? What were the effects of these exchanges on the idea or artefact being transferred? Focussing on contact between England, France and Ireland, a team of specialists explores the translation, appropriation and circulation of cultural products and scientific ideas during the Enlightenment. Through analysis of literary and artistic works, periodicals and official writings contributors uncover: • the key role played by literary translators and how they adapted, naturalized and sometimes distorted plays and novels to conform to new cultural norms; • the effects of eighteenth-century anglomania, and how this was manifested in French art; • how the vagaries of international politics and conflict affected both the cultural products themselves and the modes of dissemination; • how religious censorship engendered new Irish Catholic and French Huguenot diasporas, with their particular intellectual pursuits and networks of exchange; • the significance of newspapers and periodicals in disseminating new knowledge and often radical philosophical ideas. By exploring both broad areas of cultural activity and precise examples of cultural transfer, contributors to Intellectual journeys reveal the range and complexity of intellectual exchange and its role in the formation of a truly transnational Enlightenment. Lise Andries, Frédéric Ogée, Darach Sanfey and John Dunkley, Introduction I. Translation Samuel Baudry, Imitation and translation: the debate in eighteenth-century Britain and Ireland Garry Headland, Arthur Murphy: adapter, imitator and translator Seán Patrick Donlan, ‘If my labour hath been of service’: translating Thomas Nugent, c.1700?-1772 John Baker, Lost and found in translation: adapting and adopting Young – from the Night thoughts to the Nuits d’Young, passing by the Love of fame Pierre Degott, ‘Let me have the credit of the translation’: French and English operatic adaptations of Tom Jones II. Art and literature John Dunkley, Destouches and the London theatre: the 1722 performance of L’Ingrat and after Anne Richardot, L’histoire anglaise à la française Lise Andries, La littérature de faits divers criminels en France et en Angleterre Emma Barker, Greuze and England III. The circulation of knowledge Ann Thomson, Toland, Dodwell, Swift and the circulation of irreligious ideas in France: what does the study of international networks tell us about the ‘radical Enlightenment’? Darach Sanfey, ‘Un redoutable talent pour la dispute’: Montesquieu and the Irish Máire Kennedy, Irish booksellers and the movement of ideas in the eighteenth century Sarah Easterby-Smith, Cross-Channel commerce: the circulation of plants, people and botanical culture between France and Britain, c.1760-c.1789 IV. The press Alexis Lévrier, Justus Van Effen, un ‘passeur’ entre les presses anglaise et française Anne-Marie Mercier, Les échanges culturels entre Français et Anglais: vers une meilleure compréhension? L’exemple de la presse (L’Esprit des journaux) entre 1772 et 1785 Muriel Collart and Daniel Droixhe, Grandeur et décadence des Patagons? De la Critical review à L’Esprit des journaux (1767-1780) Allison Neill-Rabaux, A Literary journal: a forum for exchange in Ireland? Vladislav Rjéoutski, Cas de transfert culturel triangulaire: Grande-Bretagne–France–Russie: le Journal des sciences et des arts de Philippe Hernandez, Moscou, 1761 Summaries List of contributors Bibliography Index